Development Of A Teacher’s Guidebook For Organizing Eduplay Zone Play Activities For Early Childhood Based On Children’s Interests - Suryani, Ninin; Imamah; Priyanti, Nita (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2025)
This study develops “MUMTAZ” flashcards as an innovative medium to improve the speaking skills of young children with speech delay. The background arises from the fact that many children at TKIT Al-Qana, North Tambun, show limited vocabulary, unclear articulation, and difficulty forming sentences, influenced by monotonous learning media and reduced verbal interaction due to gadget use. The research employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants were 15children aged 3–6 years with speech delay, while teachers and the principal acted as supporting informants. Data collection was conducted through observation, interviews, and expert validation involving material, language, and media specialists. Validation results indicated very high feasibility, with an average score of 88.7%. Implementation in classroom learning showed significant progress: children who were previously silent or used gestures began to pronounce simple words, improve articulation, and formshort sentences. The number of children in the “less developed” category decreased to zero, while “developed” and “exceeding development” categories increased. These findings align with socio-cultural, cognitive, and behaviorist theories, emphasizing the role of interactive and dialogic media in language development. The “MUMTAZ” flashcard is therefore recommended as a valid, practical, and effective tool for teachers, parents, and therapists in supporting early childhood learning.